2020
DOI: 10.1167/tvst.9.10.10
|View full text |Cite
|
Sign up to set email alerts
|

Artifact Rates for 2D Retinal Nerve Fiber Layer Thickness Versus 3D Neuroretinal Rim Thickness Using Spectral-Domain Optical Coherence Tomography

Abstract: Purpose To compare the rates of clinically significant artifacts for two-dimensional peripapillary retinal nerve fiber layer (RNFL) thickness versus three-dimensional (3D) neuroretinal rim thickness using spectral-domain optical coherence tomography (SD-OCT). Methods Only one eye per patient was used for analysis of 120 glaucoma patients and 114 normal patients. For RNFL scans and optic nerve scans, 15 artifact types were calculated per B-scan and per eye. Neuroretinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Several studies have demonstrated high rates of errors on peripapillary RNFL segmentation in glaucomatous eyes. 4 7 , 14 , 15 Mansberger et al 5 have found that automated OCT machine data resulted in a 1.6 μm thinner RNFL thickness than the ground-truth measurements determined by manual refinement. Manual refinement changed 8.5% of scans to a different global glaucoma classification wherein 23.7% of borderline classifications become normal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated high rates of errors on peripapillary RNFL segmentation in glaucomatous eyes. 4 7 , 14 , 15 Mansberger et al 5 have found that automated OCT machine data resulted in a 1.6 μm thinner RNFL thickness than the ground-truth measurements determined by manual refinement. Manual refinement changed 8.5% of scans to a different global glaucoma classification wherein 23.7% of borderline classifications become normal.…”
Section: Resultsmentioning
confidence: 99%
“…However, the scans can be affected by movement, media opacity, algorithm failure or poor signal to noise ratios and misidentification of the anterior and posterior boundaries of the RNFL and incomplete segmentation are artifacts that are consistently described in glaucoma eyes 4 6 . In some studies, the artifact rates of 46.3% and 61.7% for OCT B scans in glaucoma eyes were reported 4 , 7 . Such errors may cause false measurements of the thicknesses of the different layers and structures.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the myopic changes were more substantial (p = 0.001) than the hypermetropia (p = 0.031). Ganglion cell thickness (GCL) studies have shown a greater GCL thinning in people with high myopia than in people with moderate and low myopia [23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of high-density MDB rim measurements in 3D space is that more data is obtained, resulting in fewer unusable scans. Park et al [ 36 ▪▪ ] showed that the 3D MDB thickness parameter has only 15.8% unusable scans, compared with 2D RNFL thickness with 61.7% unusable scans.…”
Section: The Optic Nerve: Minimum Distance Band and Three-dimensional...mentioning
confidence: 99%